Public administration in perspective : theory and practice through multiple lenses - Farmer, David John (London, United Kingdom : Routledge, Taylor & Francis Group, 2015)
Throughout its history, public administration has used a number of different perspectives for analyzing the discipline's theory and practice, and both mainstream and alternative lenses have produced valuable insights and prescriptions. At the same time, an individual way of looking at PA can be misleading. Alone, a solitary lens can miss critical aspects and often gives only part of the picture. Public Administration in Perspective has been specifically crafted to give new life to public administration theory and practice by helping readers view the discipline through a variety of perspectives. Designed for the capstone course in public administration programs, as well as a fresh approach for courses in PA theory and organizational theory, this unique book provides a culminating experience--bringing together what has been learned in previous MPA courses without simply rehashing old content. It offers a comprehensive guide to eleven major approaches to PA, and synthesizes them to deepen our understanding of the discipline. Each chapter in Part I describes the key features of the selected perspective--history, content, and proponents--and discusses the strengths and weaknesses related to PA theory and practice. Part II synthesizes the various perpectives, with specific implications for PA management and practice. Part III concludes with a complete overview, identifying ways in which readers can think more creatively and productively about PA, putting the perspectives themselves into perspective.
Public administration in perspective -- Public administration from a traditional perspective -- Public administration from a business perspective -- Public administration from an economic perspective -- Public administration from a political perspective -- Public administration from a critical theory perspective -- Public administration from a post-structural perspective -- Public administration from a psychoanalytic perspective -- Public administration from a neuroscience perspective -- Public administration from a feminist perspective -- Public administration from an ethical perspective -- Public administration from a data perspective -- Synthesizing: for public administration planning -- Synthesizing: for public administration managing --Synthesizing: for what underlies public administration -- Synthesizing: for the public administration field -- Synthesizing: for imaginative creativity --Contemplating: Public administration on a treadmill?
Includes bibliographical references and index.
Keywords: PUBLIC ADMINISTRATION